Analisis Pengaruh Karakteristik Syariah Marketing Terhadap Kepuasan Nasabah Bank Syariah Indonesia KC Jambi Gatot Subroto - Mia Awdina; Ridhwan .; Muhammad Roihan (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This research aims to analyze the influence of sharia marketing characteristics consisting of theistic, ethical, realistic and humanistic on customer satisfaction. This type of research is quantitative research. This research was conducted on customers of Bank Syariah Indonesia KC Jambi Gatot Subroto and the number of samples used was 100 respondents. Samples were taken based on the probability sampling method. Data collection was carried out by distributing questionnaires. The data analysis technique used is multiple linear regression with the help of the SPSS version 26 analysis tool. Hypothesis testing shows that the four independent variables, namely theistic, ethical, realistic and humanistic, are proven to partially and simultaneously have a positive and significant effect on the dependent variable, namely customer satisfaction.